A multi-output AC/DC energy conversion system for grid integration of bioelectrochemical power-to-gas storage - Shahparasti, Mahdi; Rajaei, Amirhossein; Tarrassó, Andres; Luna, Alvaro (Elsevier, 2022)
Bioelectrochemical Energy Storage (BES) systems are able to convert electrical power into biomethane and resemble the structure of fuel cells, as several low voltage modules are connected in series creating stacks, which are in turn parallelized to reach the desired power. However, in this case, BES modules act as gas energy storage/load that generate storable biomethane as a product. This paper proposes a multi-output multilevel AC/DC power conversion system for BES stacks. The proposed topology has a structure like a modular multi-level converter (MMC) wherein BES stacks are connected to submodules and only a capacitor exists in the DC link. Therefore, it needs only a small filter on the AC side while voltages and powers of all BES stacks are simultaneously under control. A mathematical model of the proposed power conversion system is presented, and then a control scheme has been designed in order to achieve the following goals: 1) simultaneous control of all output voltages; 2) independent control of the active and reactive power interchanged with the grid; 3) control the quality of grid current; 4) suppression of circulating current. For verification of the system performance, OPAL-RT real-time simulation results that are obtained from a 10-kW BES system containing 18 stacks are presented.
Keywords: AC/DC power Conversion; Bioelectrochemical energy storage (BES); Hardware-in-the-loop (HIL); Modular multi-level converter; fi=Sähkötekniikka|en=Electrical Engineering|